Pelatihan Pembukuan Sederhana Bagi UMKM untuk Meningkatkan Pengelolaan Keuangan Usaha di Kelurahan Kedungkandang Malang - Gaguk Apriyanto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the national economy, but the majority of MSME actors in Kedungkandang Village, Malang City still face obstacles in managing business finances. The main problems faced are the lack of separation of personal and business finances, unsystematic recording of transactions, and inability to prepare simple financial reports. This condition has an impact on the difficulty of MSME actors in knowing the real financial condition of the business, calculating accurate profit and loss, and accessing capital from financial institutions. The purpose of this community service activity is to improve the understanding and skills of MSME actors in doing simple bookkeeping as a basis for better business financial management. The implementation method includes lectures, direct practice, and mentoring by involving 25 MSME actors as participants. The material provided includes the basic concept of bookkeeping, recording cash transactions, calculating cost of goods sold, and preparing simple income statements. The results showed a significant improvement in participants' understanding, with an average pre-test score of 45.2 increasing to 82.6 in the post-test. As many as 92% of participants were able to record daily transactions correctly and 76% managed to compile a simple profit and loss report. This activity has a positive impact on the managerial ability of MSME actors in managing business finances.